2022
DOI: 10.1021/acsami.2c17627
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Immune Responses to Mucosa by Functionalized Chitosan-Based Composite Nanoparticles as a Vaccine Adjuvant for Intranasal Delivery

Abstract: Nasal administration for vaccine delivery is a novel non-invasive vaccine administration approach that can induce local or systemic immune responses and overcome the disadvantages caused by traditional injectable administration. However, mucosal vaccine and adjuvant delivery systems with sustained-release ability and enhanced immune effects at mucosal sites have still been highly demanded. In this work, N-2-hydroxypropyl trimethyl ammonium chloride chitosan/N,O-carboxymethyl chitosan nanoparticles (N-2-HACC/CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…As detailed Table 2, different polymers were explored, including protamine (PR), dextran sulphate (DX), chitosan (CS) and PEG-PGA (PP), aiming to modify the surface of the nanocarriers and enhance their uptake by dendritic cells and, hence, their immunogenic properties. These polymers have previously been used as adjuvant and antigen delivery systems, capable of activating different T and B cell responses [28][29][30][31][32]. NE-mRNAs were prepared using two distinct strategies.…”
Section: Resultsmentioning
confidence: 99%
“…As detailed Table 2, different polymers were explored, including protamine (PR), dextran sulphate (DX), chitosan (CS) and PEG-PGA (PP), aiming to modify the surface of the nanocarriers and enhance their uptake by dendritic cells and, hence, their immunogenic properties. These polymers have previously been used as adjuvant and antigen delivery systems, capable of activating different T and B cell responses [28][29][30][31][32]. NE-mRNAs were prepared using two distinct strategies.…”
Section: Resultsmentioning
confidence: 99%
“…791,792 To evaluate the adjuvant properties and mucosal immune response of chitosan derivative nanoparticles, Zhao and co-workers developed bovine serum albumin (BSA)loaded N-2-hydroxypropyl trimethyl ammonium chloride chitosan/N,O-carboxymethyl chitosan nanoparticles (N-2-HACC/CMCS/BSA NPs). 793 Both in vitro and in vivo studies revealed enhanced BSA antigen uptake in dendritic cells for these chitosan nanoparticles, as opposed to the antigen alone. The nanoparticles exhibited prolonged antigen retention in mucosal tissues even after 8 h post immunization, confirming the antigen-protective quality of the nanoparticle.…”
Section: Vaccinesmentioning
confidence: 96%
“…Thus, chitosan is often modified with other functional groups to overcome this solubility problem, thereby enhancing its effectiveness as a mucosal vaccine strategy. Nanoparticles prepared from chitosan derivatives are some of the most promising designs to enhance mucosal immunity. , To evaluate the adjuvant properties and mucosal immune response of chitosan derivative nanoparticles, Zhao and co-workers developed bovine serum albumin (BSA)-loaded N -2-hydroxypropyl trimethyl ammonium chloride chitosan/ N , O -carboxymethyl chitosan nanoparticles (N-2-HACC/CMCS/BSA NPs) . Both in vitro and in vivo studies revealed enhanced BSA antigen uptake in dendritic cells for these chitosan nanoparticles, as opposed to the antigen alone.…”
Section: Applicationsmentioning
confidence: 99%
“…Using the ionic crosslinking method, Lin et al developed a chitosan nanoparticle system with high antigen loading and mucosal absorption capacity for sustained immunization effect. Using bovine serum albumin as a model antigen, the authors demonstrated that the particles with excellent biostability and mucosal absorption could efficiently stimulate the proliferation of lymphocytes and the release of associated pro-inflammatory substances, therefore stimulating particular mucosal and systemic immune responses when administered nasally [261].…”
Section: Bioimagingmentioning
confidence: 99%